CAEP 2018 Academic Symposium: Recommendations for developing and supporting Global Emergency Medicine in Canadian academic emergency departments and divisions. Issue 5 (September 2019) - Collier, Amanda; Marton, Gregory; Chun, Shannon; Nijssen-Jordan, Cheri; Bartels, Susan A.; Pulfrey, Simon; Lang, Eddy; Schull, Michael; Landes, Megan; Johnson, Kirsten
ABSTRACT: Objectives: The objective of the CAEP Global Emergency Medicine (EM) panel was to identify successes, challenges, and barriers to engaging in global health in Canadian academic emergency departments, formulate recommendations for increasing engagement of faculty, and guide departments in developing a Global EM program. Methods: A panel of academic Global EM practitioners and residents met regularly via teleconference in the year leading up to the CAEP 2018 Academic Symposium. Recommendations were drafted based on a literature review, three mixed methods surveys (CAEP general members, Canadian Global EM practitioners, and Canadian academic emergency department leaders), and panel members' experience. Recommendations were presented at the CAEP 2018 Academic Symposium in Calgary and further refined based on feedback from the Academic Section. Results: A total of nine recommendations are presented here. Seven of these are directed towards Canadian academic departments and divisions and intend to increase their engagement in Global EM by recognizing it as an integral part of the practice of emergency medicine, deliberately incorporating it into strategic plans, identifying local leaders, providing tangible supports (i.e., research, administration or financial support, shift flexibility), mitigating barriers, encouraging collaboration, and promoting academic deliverables. The final two recommendations pertain to CAEP increasing its own engagement and support of Global EM. Conclusions: These recommendations serve as guidance for Canadian academic emergency departments and divisions to increase their engagement in Global EM.